Using Adjacent Categories Logit Model to determine the important factors influence the family income - Jassim Nassir Hussai; Sora Amer Mahmoud Al-fatlawi (Iraqi Journal for Administrative Sciences, 2024)
The family income was defined as the collection of the family members income. Therefore, when we analysis the family income data we find these data are ordinal type. Thus, the ordinal logistic model was used, which is defined as a regression analysis when the dependent variable is qualitative. It is a predicting analysis used to describe the relationship between a dependent variable and one or more of independent qualitative or quantitative variables. Adjacent Categories Logit Model is used, which is one of the ordinal logistic regression models to analysis the data when the dependent variable is ordinal. We apply this model to analysis the family income data which are collected by using a questionnaire and use STATA.14.2 software to get the results.